Rural Living in Nepal: Housing, Water & Waste in Paanchkhal - Ghimire, Labanya Devi; Lamichhane, Shamila; Lamichhane, Samir (NPRC Journal of Multidisciplinary Research, 2025)
Background: Poor housing conditions, waste disposal, sanitation and water supply system of community is directly associated with the adverse health conditions of inhabitants. Their improvement is fundamental to improving health and raising living standards of the people. Studies from developing countries like Nepal have suggested for the need of improving healthy housing conditions to enable the people to lead a healthy and productive life. Similarly, studies have also suggested that proper disposal of household waste and the provision of safe drinking water to the communities remains as the major challenge to the national and local governments of developing countries like Nepal. Objective: The objective of this study was to assess the housing conditions and provisions for household waste disposal, drinking water source, storage and treatment in the selected rural communities of Paanchkhal Municipality, Kavrepalanchowk district, Nepal. Methods: A descriptive cross-sectional study was conducted using a self-administered semi-structured questionnaire collecting primary data from 124 household heads of the study community. Descriptive statistics like frequency, percentage, mean and standard deviation were used in data analysis. Results: The mean household size was (4.84 SD ±1.99). Slightly more than half (53.23%) of houses were of Pakka type with little more than one-third (37.90%) having separate kitchen inside or outside house and little over half (55.64%) of households reported of using firewood as the main source of fuel for cooking. All except two study households (98.38%) had latrine in house or premise and the large majority of which were improved ones (86.88%). Composting (37.09) and burning (27.42%) were the two most commonly used methods of household waste disposal. River was the common source of water for a little more than one-third (37.09%) of households with large majority using plastic container for storage. Three-fourth of households (75%) reported of practicing drinking water purification with filtering being the most commonly reported method used (37.09%). Nearly three-fourth (71.77%) of household stored water in plastic container and all but three study households (98.57%) reported of covering of water stored in house. Conclusion: Nearly half of study households were of Kachcha type with about one-third having separate kitchen inside house. Majority households resorted to firewood for cooking. Large majority of households had improved latrines. Composting was the most commonly used waste disposal method. Over one-third of households relied on river as the main water source and three-fourth practiced drinking water purification.